Contribution of Urban Agriculture at Household Level in Northern Vietnam: Case Study in Trau Quy Town, Gia Lam District, Hanoi City - Phuong , Mai Lan; Le, Nguyen Phuong; Lebailly, Philippe (Asian Journal of Agriculture and Rural Development, 2017)
Similar to many developing countries, urbanization has been happening in Vietnam with bigger scale and higher speed for two recent decades. Urbanization has strongly impacted on livelihood of people those who used to be farmers. These new urban residents are facing with lack of employment, food insecurity and food unsafety. Based on quantitative and qualitative data which have been collected from 40 households by survey, in-depth interview and group-focused discussion, this study tries to show that agriculture still plays important roles in socio-economic lives of households in Trau Quy town where most of farmers have been turned into non-farmers and they lost almost all their farmland due to urbanization. The research results witness that, for economic aspect, urban agriculture contributes to households’ income, food security, food safety, and creates job opportunities for family labours, especially for those who cannot find off-farm jobs in labour market. Regard with social aspect, livelihood security and maintenance of traditional social networks are considered as significant roles of urban agriculture.